2021
DOI: 10.1186/s13756-021-00890-2
|View full text |Cite
|
Sign up to set email alerts
|

Candida tropicalis distribution and drug resistance is correlated with ERG11 and UPC2 expression

Abstract: Background Candida tropicalis (C. tropicalis) is an important opportunistic pathogenic Candida species that can cause nosocomial infection. In this study, we analyzed the distribution and drug susceptibility of C. tropicalis and the relationship between ERG11 and UPC2 expression and resistance to azole antifungal agents. Methods C. tropicalis was cultured and identified by Sabouraud Agar Medium, CHROM Agar Candida and ATB tests (Bio-Mérieux, France… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…29 ErG11 and UPC2 overexpression level were related to the reduction of fluconazole susceptibility in C. tropicalis fungemia. 30 When applying the EUCAST CBPs, 21 (55.3%) of the C. albicans isolates and 18 (37.5%) of the C. tropicalis isolates were categorized as intermediate anidulafungin susceptibility. However, according to the CLSI CBPs, these isolates were reported as anidulafungin susceptibility result.…”
Section: Discussionmentioning
confidence: 99%
“…29 ErG11 and UPC2 overexpression level were related to the reduction of fluconazole susceptibility in C. tropicalis fungemia. 30 When applying the EUCAST CBPs, 21 (55.3%) of the C. albicans isolates and 18 (37.5%) of the C. tropicalis isolates were categorized as intermediate anidulafungin susceptibility. However, according to the CLSI CBPs, these isolates were reported as anidulafungin susceptibility result.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Thailand, clinical ARCP isolates belonging to the close-related DST225 and DST506 have also been described (Tulyaprawat et al, 2020;Boonsilp et al, 2021). (Castanheira et al, 2020) Detection of genes overexpressed by qPCR CDR1 (Fan et al, 2019;Teo et al, 2019) MDR1 (Kanoshiki et al, 2015;You et al, 2017a;Jin et al, 2018;Fan et al, 2019;Teo et al, 2019;Khalifa et al, 2022) UPC2 (Jiang et al, 2016, 2;Wang et al, 2021;Khalifa et al, 2022) ERG11 (Jiang et al, 2013;Kanoshiki et al, 2015;Jin et al, 2018;Fan et al, 2019;Teo et al, 2019;Wang et al, 2021;Khalifa et al, 2022) CDR2 (Khalifa et al, 2022) CDR3 (Khalifa et al, 2022) TAC1 (Khalifa et al, 2022) HMG (Khalifa et al, 2022) FKS1 1,3-beta-glucan synthase componente in Candida Hot Spot1 F650S (Castanheira et al, 2020) S654P (Castanheira et al, 2020;Sfeir et al, 2020) S645P (Grosset et al, 2016;Khan et al, 2018b;Chew et al, 2019b;Dıáz-Garcıá et al, 2021) S80S/P (Jensen et al, 2013;Sfeir et al, 2020) R656G/R (Dıáz- Garcıá et al, 2021) S80P (Xiao et al, 2018b;Sfeir et al, 2020) D648V (Chew et al, 2019b) F641S/L (Chew et al, 2019b;Sfeir et al, 2020) Hot Spot 2 M1235I…”
Section: Mutations Referencementioning
confidence: 99%
“…The burden of antifungal-resistant Candida tropicalis in humans, animals, and the environment Recent evidence points out that there is an increasing prevalence of fluconazole and multidrug resistance among C. tropicalis recovered from humans (Favarello et al, 2021;Wang et al, 2021). In China, some centers report a prevalence of 20-50% of fluconazole non-susceptibility among C. tropicalis clinical isolates (Fan et al, 2019;Wang et al, 2020;Wang et al, 2021), while in Algeria and Japan, reports show that more than 30% of C. tropicalis bloodstream isolates are fluconazole-resistant (Megri et al, 2020;Khalifa et al, 2022). In Turkey, a recent multicentric study showed that over 10% of the bloodstream isolates collected from 2017 to 2019 are resistant to fluconazole (Arastehfar et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…C. tropicalis is widely distributed in nature, being a common colonizer of the human skin, oral cavity, and digestive tract. This yeast is an important opportunistic pathogen capable of causing nosocomial infections and it is the second most frequently isolated species after C. albicans [ 5 , 6 ]. An important aspect that contributes to invasive candidiasis is drug resistance, and in recent years, this biological trait has increased among the C. tropicalis clinical isolates [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This yeast is an important opportunistic pathogen capable of causing nosocomial infections and it is the second most frequently isolated species after C. albicans [ 5 , 6 ]. An important aspect that contributes to invasive candidiasis is drug resistance, and in recent years, this biological trait has increased among the C. tropicalis clinical isolates [ 6 , 7 , 8 ]. The main reason for C. tropicalis ’ increased drug resistance is due to mutations of the ergosterol synthase encoding gene ERG11 and overexpression of the transcriptional regulator encoded by UPC2 ( Figure 1 ) [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%